On the Enrichment of Static Functional Test - Bareiša, E.; Jusas, V.; Motiejūnas, K.; Šeinauskas, R. (Elektronika ir Elektrotechnika, 2009)
The testing problem is becoming the most crucial part of overall design process that delays the time-to-market of the digital devices. In order to alleviate the test generation complexity and to reduce the time-to-market, one needs to begin the test design at higher levels of abstraction. In this paper a new approach for static functional test enrichment is described. The enriched test pattern set may detect some pin pair faults that are not detectable on the initial test pattern set or, at least, increases the number of detections of pin pair faults. The test enrichment procedure does not increase the test size and it is fast because the procedure does not require test generation. The described approach enriches the test patterns using pin pair fault simulation. The performed experiments demonstrated effectiveness of the proposed approach. We showed that our test enrichment procedure can be incorporated into test generation system and then used as dynamic test enrichment procedure or after slight modification; it can be applied for relaxation of test pattern sets. Ill. 1, bibl. 30 (in English; summaries in English, Russian and Lithuanian).